The Effect of Heavy Metal Pollutants on Bioluminescence Intensity of Luminous Mushrooms (Nenothopanus sp) - Witriani Marvinatur Ihsan; Ratnawulan Ratnawulan (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
In the South Coastal Forest area, West Sumatra, a luminous mushroom with the species Neonothopanus Sp. This research was conducted with the aim of seeing the effect of heavy metals on the bioluminescence reaction of luminous mushrooms. Starting from the effect of heavy metal concentrations on the intensity and inhibition coefficient of luminous mushroom biolumination. From the measurement results, the maximum intensity value of luminous mushrooms is 499.6 au occurring at a wavelength of 505 nm. At a wavelength of 505 nm, visible light is produced in green. The results obtained are in accordance with observations, because the light emitted by the glowing mushroom is green. If the concentration of heavy metals is greater, the intensity of the bioluminescent fungus (Neonothopanus sp) will decrease. The type of heavy metal affects the intensity of the fungus biolumination. The greatest decrease in intensity occurred in copper (Cu) and iron (Fe), zinc (Zn) and lead (Pb). If the heavy metal concentration is greater, the inhibition coefficient will be smaller. The greatest inhibition coefficient due to the presence of heavy metals occurs in copper (Cu) then iron (Fe), zinc (Zn) and the smallest is lead (Pb).